THE INNOVATIVE POSSIBILITIES IN THE AGRO-INDUSTRIAL COMPLEX IN TERMS OF ECONOMIC SECURITY - Gridneva Yelena Evgenievna; Kaliakparova Gulnar Shaimardanovna; Alpysbayev Kaisar Serikuly; Sevindik Tuncay (Scientific Journal of Pedagogy and Economics, 2019)
In terms of integration in the agricultural production of the Republic of Kazakhstan, it is necessary to consider the peculiarities of socio-economic development, natural conditions, seasonality of production and traditions of the regions. Integration processes occurring in the industries aimed at ensuring economic and food security. The formation of the agri-food market requires the use of new forms of integration, which have an effective impact on its development and formation. The article discusses the main factors affecting the effective development of the agricultural sector.